Старожитності поморсько-кльошової культури на поселенні біля с. Хрінники (уроч. Шанків Яр) - Козак, Д.Н.; Шита, Т.М. (Археологія, 2009)
У статті подаються матеріали поморсько-кльошової культури з поселення біля с. Хрінники Рівненської обл. отриманіпід час досліджень у 2002—2007 рр. В статье проанализированы материалы поморско-клешевой культуры с многослойного памятника возле с. Хринныкы (ур. Шанкив Яр) в Ривненской области. На поселении, которое существовало с IV в. до н. э. до начала I в. до н. э., выделено две фазы: I — конец IV/начало III — середина III вв. до н. э.; II — вторая половина II — начало I вв. до н.э. Керамический комплекс поселения отражает процесс латенизации племен Волыни в указанный период. Материалы свидетельствуют, что поморско-клешевые группы населения продвигались на территорию Западной Украины с уже сформированной культурой. Археологические данные с территории Волыни дают возможность косвенно подтвердить их контакты с племенами лежницкой, черепино-лагодовской и могилянской групп раннего железного века. Материалы памятника в Хринныках свидетельствуют о том, что поморско-клешевые древности продолжали существовать до прихода на эти земли племен пшеворской культуры. Контакты с зарубинецкой культурой прослеживаются с конца II — начала I вв. до н.э. In the article the materials of Pomorsko-Klyoshova culture from a multilayer monument near Khrinnyky village (Shankiv Yar tract) in Rivne Oblast are analysed. At the settlement which existed since the 4 th c. BC till the beginning of the 1 st c. BC two phases have been traced: I) since the end of the 4 th or the beginning of the 3 rd till the middle of the 3 rd c. BC; II) since the second half of the 2 nd through the beginning of the 1 st c. BC. The ceramic complex of the settlement reflects the process of Latenization of tribes at this period. The materials testify the movement of Pomorsko-Klyoshova culture population groups, having already moulded culture, towards the territory of the Western Ukraine. Archaeological data from the territory of Volyn region allow the authors to confirm indirectly about the relations of this population with tribes of Lezhnytska culture, Cherepynsko-Lahodivska and Mohylyanska groups of the Early Iron Age. Materials from a monument in Khrinnyky testify that antiquities of Pomorsko-Klyoshova culture continued to exist up to the rise of Pshevorska culture here. Contacts with Zarubynetska culture are traced from the end of the 2 nd c. BC or the beginning of the 1 st c. BC.